Balancing theoretical and practical relevance in supply chain management research. Issue 5 (4th June 2018) - Stentoft, Jan; Rajkumar, Christopher
Abstract : Purpose: The discussion of rigor vs relevance is an ongoing debate in academic environment. Ambitions to fulfill one of these two objectives might not exclude the other. Instead, they could and should be achieved simultaneously. However, what seems to be missing in supply chain management (SCM) research is the unfolding of symmetrical balance between the two dimensions of relevance – theoretical vs practical relevance. The purpose of this paper is to advance the understanding of this symmetrical balance and to change the conversation to also include the practical relevance dimension. Design/methodology/approach: The paper is based on literature studies as well as the results of a questionnaire survey distributed to the Danish Supply Chain Panel consisting of 113 supply chain executives (as per the beginning of 2017). A short interview about the questionnaire results was also carried out with three panel members. Findings: With an increased focus on journal rankings, there is a risk of pursuing more theoretically relevant SCM research at the expense of practically relevant SCM research. Both types of relevance are important for growing the discipline. But the current development seems to favor theoretical relevance, further widening the gap with respect to practical applications. Practical relevance is important both in the knowledge production and in the knowledge transfer stages. Research limitations/implications: There is a need to further explore different resources to close the gap between theoretical and practical relevance in SCM research. Researchers ought to follow an ambidextrous research strategy. This paper advises to bring back the core of the profession – the research process. This paper encourages researchers to be more creative and intensify the focus, equally, on both the theoretical and practical relevance in their research. Practical implications: This research showcases a variety of different approaches for researchers to engage with practice so as to reduce any prejudices from both sides and enhance SCM decision-making processes. This paper recommends adding a new type of paper "practical paper" and including practitioners in the review board to evaluate the practical content of the research paper. This initiative would strengthen the interaction between researchers and practitioners. Originality/value: This paper provides new insights on the need for symmetrical balance between theoretical and practical relevance being important for both academia and practice.